The beginnings of Islamic law - Salaymeh, Lena, 1944- (Cambridge)
xiii, 242 sayfa
Keywords: “The Beginnings of Islamic Law is a major and innovative contribution to our understanding of the historical unfolding of Islamic law. Scrutinizing its historical contexts, the book proposes that Islamic law is a continuous intermingling of innovation and tradition. Salaymeh challenges the embedded assumptions in conventional Islamic legal historiography by developing a critical approach to the study of both Islamic and Jewish legal history. Through case studies of the treatment of war prisoners, circumcision, and wife-initiated divorce, she examines how Muslim jurists incorporated and transformed 'Near Eastern' legal traditions. She also demonstrates how socio-political and historical situations shaped the everyday practice of law, legal education, and the organization of the legal profession in the late antique and medieval eras. Aimed at scholars and students interested in Islamic history, Islamic law, and the relationship between Jewish and Islamic legal traditions, this book's interdisciplinary approach provides accessible explanations and translations of complex materials and idea“ --